The use of endoanchors in repair EVAR cases to improve proximal endograft fixation - Avci, Murat; Böckler, Dittmar (The journal of cardiovascular surgery, 2012)
AIM: The aim of this paper was to evaluate short-term outcome of the use of endoanchors to secure the primary migrated endograft and additional extender cuffs to the aortic wall in patients with previous failed endovascular aortic aneurysm repair. METHODS: Consecutive patients who needed proximal repair of a primary failed endograft due to migration (with or without type IA endoleaks) were treated with endoanchors, with or without additional extender cuffs. Data of this group were prospectively gathered in vascular referral centers that were early adopters of the endoanchor technique. Preprocedural and periprocedural data were prospectively gathered and retrospectively analyzed. Follow-up after endoanchor placement consisted of regular hospital visits, with computed tomography or duplex scanning at 1, 6, and 12 months. RESULTS: From July 2010 to May 2011, 11 patients (8 men), mean age 77 years (range, 59-88 years), were treated with endoanchors for a failed primary endograft (2 Excluder endografts, 1 AneuRx endograft, and 8 Talent endografts) due to distal migration of the main body, with or without type IA endoleak. Revision consisted of using endoanchors to secure the body of the primary endograft to the aortic wall to avoid persistent migration. Most patients had additional proximal extender cuffs with suprarenal fixation, which were secured with endoanchors to the aortic wall and in some patients also to the primary endograft. A median of 6 endoanchors were implanted. All endoanchors were positioned correctly but one. One endoanchor dislodged but was successfully retrieved using an endovascular snare. During a mean follow-up of 10 months (range, 3-18 months) no endoanchor-related complications or renewed migration of the endografts occurred. Two patients underwent repeat intervention due to persistent type IA endoleak during follow-up. CONCLUSION: The use of endoanchors to secure migrated endografts to the aortic wall is safe and feasible and might help to overcome persistent migration of primary failed endografts. In combination with the use of sole extender cuffs the majority of proximal EVAR failures can be solved.